The Defence of Anthropological Dualism in the Philosophy of Stanisław Judycki - Dobrzeniecki, Marek (Roczniki Filozoficzne, 2024)
The following paper summarizes the achievements of Stanisław Judycki in the field of philosophical anthropology. He takes the position of the absolute dualism, proclaiming the existence of the human soul as an independent being (a simple, immaterial and atemporal substance), of the Augustinian-Cartesian type (stating the possibility of capturing the “I” in the stream of one’s own consciousness, although behind the veil of semantic generality). In the text, I present Judycki’s arguments to support this position: (a) explaining such features of internal experience as the unity of the stream of consciousness is possible only in dualism, (b) the modal argument, (c) arguments against naturalism (according to Judycki, the only alternative to anthropological materialism is dualism). I also defend the view that the best arguments for dualism are arguments from group (c).